Association of Umbilical Cord Plasma Acid-labile Subunit of the Insulin-like Growth Factor Ternary Complex with Anthropometry in Term Newborns - Yen-Ming Tseng; Yea-Shwu Hwang; Chin-Li Lu; Shio-Jean Lin; Wen-Hui Tsai (Elsevier, 2014)
Birth size can affect neonatal morbidity and mortality. The insulin-like growth factor (IGF) system is the most important endocrine factor influencing fetal growth. In the circulation, IGFs (mostly IGF-I) are bound to IGF-binding protein 3 (IGFBP-3) and an acid-labile subunit (ALS) to form a ternary complex. The ALS protects IGFs from decay and facilitates their endocrine activity. However, the function of ALS in fetal growth has not yet been fully determined. Methods: Venous umbilical plasma samples were obtained from 98 term neonates and analyzed using enzyme-linked immunosorbent assays. The ALS, IGF-I, and IGFBP-3 umbilical cord plasma levels were analyzed for their association with anthropometric measurements of the neonates. Results: The ALS, IGF-I, and IGFBP-3 cord plasma levels were positively correlated with birth weight (r = 0.42, p < 0.001; r = 0.43, p < 0.001; and r = 0.27, p < 0.01, respectively) and placental weight (r = 0.37, p < 0.001; r = 0.31, p < 0.01; and r = 0.30, p < 0.01, respectively). In addition, the ALS cord plasma levels were also positively correlated with head circumference (r = 0.29, p < 0.01). Multiple linear regression analyses showed that both ALS and IGF-I cord plasma levels were independent predictive variables for birth weight (p < 0.01 and p < 0.005, respectively). The ALS cord plasma levels were the only independent predictive variables, however, for head circumference and placental weight (p < 0.01 and p < 0.05, respectively). Conclusion: The ALS umbilical cord plasma levels are one important factor, in addition to IGF-I, in the IGF system for predicting birth anthropometry, at least for near-term gestation. Our results suggest that the influence of ALS on the IGF system may develop prior to birth and affect fetal growth.